The Adsorption Process and Mechanism of Benzo[a]pyrene in Agricultural Soil Mediated by Microplastics - Zhengyi Zhu; Lijuan Sun; Qin Qin; Yafei Sun; Shiyan Yang; Jun Wang; Yang Yang; Guangkuo Gao; Yong Xue (Toxics)
The coexistence of microplastics and benzo[a]pyrene (BaP) in the environment, and their interactions within agricultural soils in particular, have garnered widespread attention. This study focused on the early-stage interactions between microplastics and BaP, aiming to uncover their initial adsorption mechanisms. Despite the significant environmental toxicity of both pollutants, research on their mutual interactions in soil is still limited. This study conducted adsorption thermodynamics and kinetics experiments to explore the effects and mechanisms of various microplastics (polyethylene (PE), polystyrene (PS), and polyvinyl chloride (PVC)) on the adsorption of BaP. Using advanced techniques such as scanning electron microscopy (SEM), X-ray photoelectron spectroscopy (XPS), and Fourier transform infrared (FTIR) spectroscopy, this study explored the surface characteristics of microplastics and their interactions with BaP. The results demonstrated that PVC microplastics exhibited the highest adsorption capacity for BaP, which was primarily due to π–π interactions and increased hydrophobicity. In the soil–microplastic blend systems, BaP was predominantly found on microplastics, enhancing the soil’s adsorption capacity for BaP, particularly PVC, which showed an adsorption capacity 3.69 times greater than that of soil alone. Density functional theory (DFT) simulation calculations indicated that the binding energy of BaP for PVC pretreated with soil was −59.16 kJ/mol, whereas it was −53.02 kJ/mol for untreated PVC, −39.35 kJ/mol for PE, and −48.84 kJ/mol for PS. These findings suggest that soil pretreatment enhances the adsorption stability of PVC for BaP, further elucidating the potential mechanisms behind the increased adsorption capacity in the soil–microplastic system. These findings confirm that microplastics serve as effective vectors for organic pollutants such as BaP, significantly influencing their environmental behavior in soils, and provide essential theoretical support for assessing the environmental toxicity and migration behaviors of microplastics and associated organic contaminants.